Use of Oral Chroma™ in the Assessment of Volatile Sulfur Compounds in Patients with Fixed Prostheses. (July 2013) - Sinjari, B.; Murmura, G.; Caputi, S.; Ricci, L.; Varvara, G.; Scarano, A.
Prosthetic rehabilitation improves the patient's quality of life and oral health. The purpose of the present study was to assess the production of volatile sulfur compounds (VSCs) using Oral Chroma™ in patients wearing provisional and permanent fixed prosthesis, who were treated or not, with supportive non-surgical periodontal therapy. A total of 10 healthy patients not affected by periodontal disease and who needed the restoration of at least two edentulous single sites were included in the present study. Registrations of VSCs were carried out with a Gas Chromatograph OralChroma™ (Oral Chroma™, Abimedical, Abilit Corp., Osaka, Japan) one month after placement of the provisional restoration (group 1) and one month after placement of the final restoration (group 3). After each measurement, professional oral hygiene was carried out both on patients with provisional (group 2) and permanent prostheses (group 4) and VSC values were registered. The results showed that there were no statistical significant differences in the VSC quantity between groups with temporary or permanent prostheses. Meanwhile, statistically significant differences were found in VCS values between groups before and after the professional health care session (p < 0.05). Also it was observed that dimethyl sulphide (CH3 )2 S was present in all the study groups. The present preliminary study suggests that OralChroma™ produce a comprehensive assessment of VSC in the clinical diagnosis of halitosis and that professional oral hygiene seems to influence VSC production. However, further clinical long-term studies with a larger sample size are necessary for a better understanding of halitosis manifestation in patients wearing provisional and permanent fixed prosthesis.